2013
DOI: 10.1121/1.4792353
|View full text |Cite
|
Sign up to set email alerts
|

Underwater sound scattering and absorption by a coated infinite plate with a distributed inhomogeneity

Abstract: This paper concerns itself with the scattering and absorption of underwater incident sound by a coated infinite plate with an attached distributed inhomogeneity. Its objective is to determine if the distributed inhomogeneity can provide additional local reflection, such that it only increases the signal-to-noise ratio for a hydrophone detector placed on the inhomogeneity without significantly decreasing the overall sound absorption of the coated plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…The stress and displacement components of the coating in Eqs. (21), (22), (23), and (24) are expressed by the coefficients A 1 , B 1 , A 2 , and B 2 , respectively, of the velocity potentials. 17 By combining Eqs.…”
Section: Modeling Of the Coated Platementioning
confidence: 99%
“…The stress and displacement components of the coating in Eqs. (21), (22), (23), and (24) are expressed by the coefficients A 1 , B 1 , A 2 , and B 2 , respectively, of the velocity potentials. 17 By combining Eqs.…”
Section: Modeling Of the Coated Platementioning
confidence: 99%
“…Previously published researches have mainly focused on the unreinforced plates coated by decoupling acoustic coating layers [1][2][3][4][5][6][7]. There are also numerous researches regarding with the reinforced structures [12][13][14][15][16][17][18][19][20][21][22], while which are not covered by decoupling acoustic coating layers.…”
Section: Introductionmentioning
confidence: 97%
“…In conjunction with the thin-plate theory, Keltie [4] formulated an analytical model for a compliant elastic coating attached to a submerged thin plate, where the normal and tangential velocity components in the coating were detailed analyzed. Taking into account the attached distributed inhomogeneity, Zhang and Pan [5,6] established a theoretical model to investigate the sound radiation and absorption properties of coated infinite plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 It was found that the finite SCP can provide the required local sound reflection without affecting the overall sound radiation and absorption of the coated plate at most frequencies. 1,2 However, at the resonance frequencies of trapped modes caused by the SCP, sound radiation can be significant while sound absorption suffers from localized resonances that have strong sound radiation capability.…”
Section: Introductionmentioning
confidence: 99%